Legal Review of Procedures for Granting Rock Mining Business Permits - Leoni, Cindy Cynthia; Sitompul, Roswita; Pakpahan, Kartina (International Journal of Business, Law, and Education, 2024)
This research is motivated by the granting of mining permits originally granted by the Central Government, with the issuance of Presidential Decree Number 55 of 2022 concerning the Delegation of Granting of Business Licensing in the Mineral and Coal Mining Sector, some mining permits are granted by the Central Government to the Provincial Government, but only limited to the granting of Mining Business Permits (IUP) for non-metallic mineral groups, certain types of non-metallic minerals, and rocks. The legal research method used in this research is normative juridical research which is research that is carried out or aimed only at written regulations with a descriptive analytical research nature which is a method that functions to describe or provide an overview of the object being studied. The data source used is secondary data with quantitative data analysis. The results of this study are: The Procedure for Rock Mining Business Permits is carried out by means of an application to the regent or mayor if the mining area is in a district or city, to the governor if the mining area is across district or city borders, to the minister if the mining area is in a cross-provincial border area. The procedures carried out in the procedures for rock mining permits are the determination of the mining area carried out by authorized officials, determination of mining business areas, mining business permits, regulation of mining permits if there is a violation of mining permits. Supervision of Rock Mining Activities After Obtaining a Business Permit in the Mining Sector, it is carried out by the ESDM Service where the mining permit is located. Settlement of Rock Mining Permit Disputes can be carried out through a non-adjudication process.